Goose Mx and OASL Play Vital Roles in the Antiviral Effects of Type I, II, and III Interferon against Newly Emerging Avian Flavivirus - Chen, Shun; Zhang, Wei; Wu, Zhen; Zhang, Jinyue; Wang, Mingshu; Jia, Renyong; Zhu, Dekang; Liu, Mafeng; Sun, Kunfeng; Yang, Qiao; Wu, Ying; Chen, Xiaoyue; et al. (Frontiers in Immunology, 2017)
Duck Tembusu virus (TMUV), an emerging avian flavivirus, is highly pathogenic to birds and has the potential to become a zoonotic pathogen. Here, the molecular antiviral mechanism of goose type I, II, and III interferon (goIFNα, goIFNγ and goIFNλ), the key components of the innate immune pathway, against TMUV was studied. We found that the transcription of goIFNs was obviously driven by TMUV infection in vivo and in vitro, and the titres and copies of TMUV were significantly reduced following treatment with goIFNs. The results of RNA sequencing (RNA-seq) revealed that goIFN stimulation triggered a set of differentially expressed genes at different levels and a positive regulatory feedback loop of IFN release against infection. Two important interferon-stimulated genes (ISGs), goMx and goOASL, were identified as workhorse IFNs in the inhibition of TMUV replication. The antiviral effects of goMx and goOASL were confirmed by transient overexpression and knockdown assay in vitro. Overall, our findings defined that goose Mx and OASL play key roles in the antiviral effects of type I, II, and III interferon against the Tembusu virus. These results extend our understanding of the transcriptional profile of the goose IFN-mediated signalling pathway and provide insight into the antiviral mechanism of goIFNs against flavivirus infection.